Psychological Characteristics of BDSM Practitioners. (16th May 2013) - Wismeijer, Andreas A.J.; van Assen, Marcel A.L.M.
Abstract: Introduction: It has been generally thought that the practice of bondage‐discipline, dominance‐submission, sadism‐masochism (BDSM) is in some form associated with psychopathology. However, several more recent studies suggest a relative good psychological health of BDSM practitioners. Aim: The aim of this study was to compare scores of BDSM practitioners and a control group on various fundamental psychological characteristics. Methods: For this aim, 902 BDSM and 434 control participants completely filled out online questionnaires. Associations were examined using χ 2 tests of independence with φ and Cramer's V as effect size measures and eta or Pearson's correlation. Group differences were tested using analysis of covariance, with partial η 2 as effect size measure. A priori contrasts were tested using α = 0.01 to correct for multiple testing; for all other tests we used α = 0.05, two tailed. Main Outcome Measures: The study used Big Five personality dimensions (NEO Five‐Factor Inventory), attachment styles (Attachment Styles Questionnaire), rejection sensitivity (Rejection Sensitivity Questionnaire), and subjective well‐being (World Health Organization‐Five Well‐being Index). Results: The results mostly suggest favorable psychological characteristics of BDSM practitioners compared with the control group; BDSM practitioners were less neurotic, more extraverted, more open to new experiences, more conscientious, less rejection sensitive, had higher subjective well‐being, yet were less agreeable. Comparing the four groups, if differences were observed, BDSM scores were generally more favorably for those with a dominant than a submissive role, with least favorable scores for controls. Conclusion: We conclude that BDSM may be thought of as a recreational leisure, rather than the expression of psychopathological processes.Wismeijer AAJ and van Assen MALM. Psychological characteristics of BDSM practitioners. J Sex Med 2013;10:1943–1952.